Potential of Pseudomonas and Trichoderma from the Brazilian Amazon as Biocontrol Agents against the Wheat Blast Disease - Pereira, Maikon Richer de Azambuja [UNESP]; Moreira, Silvino Intra [UNESP]; Silva, Abimael Gomes da [UNESP]; Nunes, Tiago Calves [UNESP]; Vicentini, Samara Nunes Campos [UNESP]; Silva, Davi Prata da [UNESP]; Silveira, Patrícia Ricardino da; Oliveira, Tamiris Yoshie Kiyama de [UNESP]; Silva, Tatiane Carla [UNESP]; Botelho, Deila Magna dos Santos; Resende, Mario Lúcio Vilela; Ceresini, Paulo Cezar [UNESP] (MDPI, 2022)
Blast is one of the most significant wheat diseases, causing high yield losses in susceptible varieties under favorable conditions in Latin America, Southeastern Asia and Eastern Africa. The disease is caused by the ascomycetous fungal pathogen Pyricularia oryzae Triticum lineage (PoTl). Chemical control with fungicides has been used as a management strategy; however, the effectiveness of the major classes of high-risk site-specific systemic fungicides has been reduced due to the widespread prevalence of resistance, especially in Brazil. Biological control is seen as a highly important and sustainable strategy to minimize the impact of yield losses associated with wheat blast in areas where fungicides are ineffective. In our study, we specifically aimed to determine the biological control potential of the three isolates of fluorescent Pseudomonas and three of Trichoderma as the antagonists of PoTl, both in in vitro and under greenhouse conditions. Additionally, we aimed to describe the ultrastructural interactions among the biocontrol agents and the pathogen in vitro by means of scanning electron microscopy (SEM). Fluorescent P. wayambapalatensis ‘Amana’ or Pseudomonas sp. nov. ‘Yara’, both from the P. putida group, and Trichoderma koningiopsis ‘Cachara’ significantly reduced PoTl in vitro mycelial growth and the blast disease severity on wheat plants. The SEM analyses revealed ultrastructural antagonistic mechanisms: biofilm formation, direct antagonism and mycoparasitism. Further research on the topic should include the development of stable formulations of the Pseudomonas- and Trichoderma-based biocontrol agents selected in our study for managing the wheat blast disease and the field tests of the biofungicide formulations obtained thereafter.
Keywords: antagonism; biocontrol; Pseudomonas; Pyricularia oryzae Triticum lineage; Trichoderma